INCREASING PROFITS IN THE BANKING SECTOR THROUGH THE OPTIMIZATION OF NPL AND LDR - Bintang Anggraini Fania Gunawan; Helmy Wahyu Sukiswo (RISTANSI: Riset Akuntansi, 2026)
This study aims to analyze the impact of managing Non- Performing Loans (NPL) and the Loan to Deposit Ratio (LDR) on the profitability of banking companies in Indonesia, measured through Return on Assets (ROA). The data utilized is secondary data with a quantitative approach, encompassing 150 data points from 30 companies whose reports were published on the Indonesia Stock Exchange during the period of 2020-2024. The analysis results indicate a significant relationship between NPL and profitability, suggesting that high NPL can negatively affect banks' profitability performance. Furthermore, a significant relationship is also found between LDR and profitability, indicating that an optimal LDR can enhance the efficiency of banks in generating profits. This research provides important insights for bank management in decision-making related to loan and deposit management.